2022
DOI: 10.1108/jadee-04-2022-0066
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rice production and the impacts of the usage of certified seeds on yield and income in Côte d'Ivoire

Abstract: PurposeAfter a long observation of the high rate of rice importation and low productivity in Côte d’Ivoire, the certified rice seed was introduced and encouraged to be used by the local farmers. This study evaluates the profitability of rice production and the impact of certified seed usage on the yield and income of farmers in Côte d’Ivoire.Design/methodology/approachData were collected from 265 rice farmers. Descriptive statistics were used to identify the challenges faced in using certified seeds. Profitabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Thus, farmers who were able to get external funding have a better standard of living than their counterparts who have no access to credit. This could be because external funding serves as a means of increasing farmers' investment and adoption of technology (Akanbi et al, 2022;Falola et al, 2022b). This supports the findings of Amfo et al (2022) that access to credit access enhances welfare.…”
Section: Factors Influencing the Welfare Status Of The Artisanal Fish...supporting
confidence: 69%
“…Thus, farmers who were able to get external funding have a better standard of living than their counterparts who have no access to credit. This could be because external funding serves as a means of increasing farmers' investment and adoption of technology (Akanbi et al, 2022;Falola et al, 2022b). This supports the findings of Amfo et al (2022) that access to credit access enhances welfare.…”
Section: Factors Influencing the Welfare Status Of The Artisanal Fish...supporting
confidence: 69%
“…The study by Akanbi et al (2022), using the PSM found that the application of certified crops is capable of increasing farm yield. The study posited that farmers that applied certified crops get a higher level of income, about $263.74/ha more than their counterparts who did not apply ($212.31/ha).…”
Section: Insights From the Literaturementioning
confidence: 99%
“…While the literature has mainly focused on specific essential drivers of agricultural productivity, such as land, credit and institutions (Akanbi et al, 2022;Khatun and Haider, 2016;Osabohien et al, 2020), not many studies have been carried out to empirically examine how the adoption of the various components of soil technology, such as fertiliser, pesticides, herbicides and certified crops, influence post-harvest losses. The rationale is that this study argues that soil technology adoption could help reduce post-harvest losses in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the majority (98%) did not belong to cooperative association in the research area for beekeeping. This could affect their ability to get financial assistance (Koşum et al, 2019;Akanbi et al, 2022).…”
Section: Socio-economic Characteristicsmentioning
confidence: 99%